The Rise of Artificial Intelligence (AI) in Public Administration: Reimagining Government Services and Delivering Value to Citizens - Fika Fibriyanita (Penelitian dan Pengembangan Ilmu, 2024)
Artificial Intelligence (AI) has become increasingly relevant in public administration due to its potential to improve decision-making processes and service delivery. This research aims to identify and analyze the impact of AI implementation on the quality of public services, as well as exploring the benefits and challenges faced in implementing AI in the public sector. Using a systematic literature review method, this research collects and analyzes relevant literature from reputable international databases, including Scopus, Web of Science, IEEE Xplore, and Google Scholar. The research results show that AI can improve efficiency, productivity and user satisfaction of public services, while presenting challenges related to ethics and privacy. The implications of this research include recommendations for governments and policymakers to expand the use of AI in various public service sectors, as well as the need to develop ethical frameworks that can help address emerging challenges. This research makes a significant contribution to the academic and practical literature by offering a holistic approach and practical recommendations for optimizing the use of AI in public administration.